2000
DOI: 10.1007/bf02236847
|View full text |Cite
|
Sign up to set email alerts
|

Stapled hemorrhoidectomy—cost and effectiveness. randomized, controlled trial including incontinence scoring, anorectal manometry, and endoanal ultrasound assessments at up to three months

Abstract: Stapled hemorrhoidectomy is a safe and effective option in treating irreducible prolapsed piles. It is more expensive but less painful, with less time needed off work. Nonetheless, long-term results are still awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
374
6
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(406 citation statements)
references
References 13 publications
11
374
6
13
Order By: Relevance
“…Various controlled trials comparing stapled haemorrhoidopexy and conventional haemorrhoidectomy have concluded that stapled haemorrhoidopexy may be associated with less post-operative pain and earlier return to work as compared to conventional haemorrhoidectomy [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Various controlled trials comparing stapled haemorrhoidopexy and conventional haemorrhoidectomy have concluded that stapled haemorrhoidopexy may be associated with less post-operative pain and earlier return to work as compared to conventional haemorrhoidectomy [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding in the immediate postoperative period is almost always due to inadequate intraoperative hemostasis. In the existing literature, this complication occurs in 4 to 25 % of cases [41][42][43][44][45][46][47][48]. Bleeding predominantly affects patients with fourth-degree hemorrhoids [49,50].…”
Section: Complicationsmentioning
confidence: 99%
“…SH is also known as procedure for prolapsed hemorrhoids (PPH). The early clinical experience showed better clinical outcome with SH compared to conventional hemorrhoidectomy [4][5][6][7][8]. Subsequently published various randomized controlled clinical studies and systematic reviews have again compared the SH with conventional hemorrhoidectomy to evaluate the short term and long term safety and effectiveness of the procedure [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%